2008
DOI: 10.1002/ange.200703955
|View full text |Cite
|
Sign up to set email alerts
|

Palladium–(S,pR)‐FerroNPS‐Catalyzed Asymmetric Allylic Etherification: Electronic Effect of Nonconjugated Substituents on Benzylic Alcohols on Enantioselectivity

Abstract: The development of efficient methods for enantioselective synthesis remains at the center of modern-day organic chemistry, as such methods have many important applications, from the total synthesis of natural products [1] to the preparation of analogues of lead compounds in the pharmaceutical industry. The ability to prepare compounds by a carbon-heteroatom bond-forming process from a common intermediate is of great significance to the drug-discovery process. In particular, the stereoselective construction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, this protocol is sometimes synthetically impractical owing to the strong basicity of the alkoxide anion, which may be incompatible with other functional groups presented in the system. [3] Therefore some modified methods were developed, [4,5,6] for example, transition metal-catalyzed cross-coupling of aryl halides with phenols or alcohols.…”
mentioning
confidence: 99%
“…However, this protocol is sometimes synthetically impractical owing to the strong basicity of the alkoxide anion, which may be incompatible with other functional groups presented in the system. [3] Therefore some modified methods were developed, [4,5,6] for example, transition metal-catalyzed cross-coupling of aryl halides with phenols or alcohols.…”
mentioning
confidence: 99%
“…In this context, although numerous chiral ligands has been reported for regioselective and enantioselective allylic alkylation with relatively good performance,4, 5 the palladium‐catalyzed asymmetric allylic alkylation or etherification (AAE) of alcohols and 1,3‐diphenyl‐2‐propenyl acetate has not been widely reported with high levels of enantioselectivity owing to the mismatch of poor nucleophilicity of alcohols with respect to chiral metal–ligand complexes 4a. 6 Notably, in 2008, Chan and co‐workers reported a palladium‐catalyzed asymmetric allylic etherification of 1,3‐diphenyl‐2‐propenyl acetate with alcohols in moderate to high yields (58–98 %) and good to excellent levels of enantioselectivity (83–96 % ee ) by using the ( S , p R )‐FerroNPS ligand 7. Meanwhile, the research groups of Hou, Ding, Fukuzawa, Du, and others8 have also demonstrated independently that various bidentate phosphine or phosphite ligands associated with palladium centers afford chiral allylic ethers in moderate to good levels of enantioselectivity and diastereoselectivity.…”
Section: Methodsmentioning
confidence: 99%
“…[4a, 6] Notably, in 2008, Chan and co-workers reported a palladium-catalyzed asymmetric allylic etherification of 1,3-diphenyl-2-propenyl acetate with alcohols in moderate to high yields (58-98 %) and good to excellent levels of enantioselectivity (83-96 %ee) by using the (S, p R)-FerroNPS ligand. [7] Meanwhile, the research groups of Hou, Ding, Fukuzawa, Du, and others [8] have also demonstrated independently that various bidentate phosphine or phosphite ligands associated with palladium centers afford chiral allylic ethers in moderate to good levels of enantioselectivity and diastereoselectivity. However, this useful process to provide chiral allylic ethers still needs substantial improvement in its level of enantioselectivity and chemical yield to be more practical.…”
mentioning
confidence: 99%
“…This functional‐group compatibility potentially offers the opportunity for additional functionalization of the chiral alkyne product by using well‐established cross‐coupling protocols 16. Some nonconjugate electronic effects of the alkene moiety on the product enantioselectivity were observed (entries 3, 6–8) 17. Electron‐donating groups on the benzonorbornadiene provided a better stereochemical outcome,18 possibly because of a more favorable coordination of CC to the chiral iridium center (entries 6 and 8).…”
Section: Methodsmentioning
confidence: 99%